2010
DOI: 10.1103/physreve.81.041702
|View full text |Cite
|
Sign up to set email alerts
|

Nematic textures in colloidal dispersions of Na-fluorohectorite synthetic clay

Abstract: We have studied stable strata of gravity-induced phase separation in suspensions of synthetic Na-fluorohectorite clay in saline solutions. We have observed how the strata depend on clay concentration as well as on salt content. The mass distribution and density variation at the isotropic-nematic interface indicate that existing models and assumptions in existing simulations are able to relatively well account for the observed behavior. We suggest that discrepancies could be due to the high polydispersity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…It was shown that at low ionic strengths (4 5.10 À3 M/L), all the interactions in the system were repulsive and that as a first approximation, most rheological features of the suspensions could be explained using arguments based on excluded volume effects. Liquid crystal behaviour was also observed recently for synthetic fluorohectorite samples (De Azevedo et al, 2007;Hemmen et al, 2009;Miyamoto et al, 2010;Ringdal et al, 2010) and for beidellite (Paineau et al, 2009), although the former samples were not fully delaminated.…”
supporting
confidence: 73%
“…It was shown that at low ionic strengths (4 5.10 À3 M/L), all the interactions in the system were repulsive and that as a first approximation, most rheological features of the suspensions could be explained using arguments based on excluded volume effects. Liquid crystal behaviour was also observed recently for synthetic fluorohectorite samples (De Azevedo et al, 2007;Hemmen et al, 2009;Miyamoto et al, 2010;Ringdal et al, 2010) and for beidellite (Paineau et al, 2009), although the former samples were not fully delaminated.…”
supporting
confidence: 73%
“…9 show that the exponent (n) slightly depends on polydispersity. Therefore, it becomes interesting to see why similar colloidal systems, such as clay, having a large size polydispersity and large aspect ratio (ξ ∼ 0.01), commonly do not exhibit a nematic, but rather a gel phase, where some orientational order should be present [41,62,64,95]. In this paper, we observed that it was polydispersity that widened φ I−N .…”
Section: The Effect Of Aspect Ratio and Polydispersity On The I-n mentioning
confidence: 83%
“…For instance, the clear-cut pieces of evidence for isotropicnematic [20,[34][35][36][37][38][39], isotropic-lamellar [21,40], and a sequential transition involving isotropic-nematic and nematiclamellar transitions [26] with increasing φ p at a particular r asp (in the range satisfying 1.1 × 10 −3 r asp 7.1 × 10 −2 ) have already been obtained by using the scattering method. However, due to the difficulty in preparing a wide variety of size-controlled particles, the experimental studies attempting to elucidate systematically the r asp dependence of the phase behavior are rather minor [22,23,[34][35][36][37][38].…”
Section: Liquid Crystalline Phasementioning
confidence: 99%